The Analysis of Hearing Threshold Level of Noise Exposed Workers in Circulator Loom Unit - Mariska Hamid (Universitas Airlangga, 2020)
Introduction: One of the hazards caused by the process of producing plastic sacks is noise. Noise is unwanted sound judged to be unpleasant, loud or disruptive to hearing. Noise is produced by machines used in the production process. Noise that exceeds the threshold limit value (TLV) at workplace can cause hearing loss. The purpose of this study was to analyze the hearing threshold level of workers who were exposed to noise in circulator loom unit at PT. Kerta Rajasa Raya Sidoarjo. Method: This was an observational study with a cross sectional approach. The population of this study was 47 workers, while the sample was the total population. The independent variable wasnoise, while the dependent variable was the hearing threshold level. Contingency coefficient was used to detemine the strength of correlation between variables. Noise intensity measurement at three points revealed that the value exceeded the time limit value. Result: Most of the workers were > 40 years old (72.3%), had work period of 15-20 years (51.07%) and never consumed ototoxic medication (80.85%). Conclusion: A moderate correlation between the noise intensity and hearing threshold level of right ear. However, the correlation between noise intensity and hearing threshold level of left ear is weak. Keywords: hearing threshold level, noise, work characteristic